RELEVANT COST MANAGEMENT TRAINING IN DETERMINING COMPETITIVE SELLING PRICES IN THE HOME INDUSTRY IN MUARA PENIMBUNG VILLAGE - Maryati, Sri; Saggaf, Abdullah; S Sitepu, CH. Damar; L Ruskan, Endang (LPPM Univ. Ibn Khaldun Bogor, 2023)
Muara Penimbung village became a gathering place for Songket weavers. Songket SMEs in Muara Penimbung Village have not been well marketed, the new songket product marketing media is done face-to-face. The solution offered to the public is to identify relevant and irrelevant costs before determining the selling price, in addition to introducing digital or online marketing media and providing ways to market their products through digital or online media so that the existing selling prices can compete and songket products in the market. know the general public. The method of implementing the service uses management assistance methods to increase the capacity of songket business actors. The systematic implementation of service activities consists of presentations, presentations, discussions, and evaluations. The Lppm team directly asked the Songket UKM community in the Muara Penimbung village regarding the relevant costs in the songket UKM of the Muara Penimbung community, how to determine relevant and irrelevant costs, and whether songket has been offered in marketing media such as Instagram and Shoope. The people of Muara Penimbung Village have a pretty good response, it can be seen from the enthusiasm of the community of songket craftsmen to find out the relevant costs in the business they are engaged in, the implementation and use of social media to promote their products have been done, one of which is by updating songket products and prices on Whataapp and Instagram statuses.